Designing Ecohouses for Irkutsk: an Ecohouse Designed on the Basis of Thermal Core and Buffer Zone - Zarubina, Anna; Saushkina, Alisa (project baikal, 2016)
The article features the principles of ecohouse design. The two ecohouses described in the article are designed for climatic conditions of Irkutsk, basing on the combination of thermal core and buffer zones, and using prefabricated units as well as local building materials.
Keywords: ecohouse; sustainable architecture; green building; energy-efficient house; frame house building